UDP-TRIZ model improvement with a focus group discussion of TRIZ experts - S., Shahrin; Khairul Aidil Azlin, Abd Rahman; Khairul Manami, Kamarudin; Rosalam, Che Me; Jamal Rizal, Razali; Imaduddin, Abidin; Mai Mariam, Mohamed Aminuddin; Izadora, Mustaffa; M. F., Abdul Jalal; Muhammad Firdhaus, Che Hassan (IOP Publishing, 2020)
Universal Design is a fundamentals of good design. A product with Universal Design approach should provide wide range of solution for people with different purposes including those with diverse disabilities. However, designers often based on a subjective understanding of Universal Design Principles (UDP) to formulate design solutions. This result in the inaccurate conversion of design needs. A systematic approach is needed in order to develop a concept to meet the customer need. Previous studies shown potential integration of the Theory of Inventive Problem Solving (TRIZ) proposed to create a systematic approach for problem-solving requires creativity abilities. The purpose of this study is to explore the construction of the integration model of UDP and TRIZ 40 inventive principles. To construct the integration model of UDP and TRIZ 40 inventive principles, this study will use focus group discussion of certified TRIZ experts in the exploration of establishing an integration model of UDP and TRIZ 40 inventive principles. The further discussion onto the elements required to create the integration model by the TRIZ experts will be taken into consideration to construct a final model UDP-TRIZ model. Finally, the results are expected to lead towards a final integration model of the UDP and TRIZ integration model.